2018
DOI: 10.1007/s10519-018-9923-1
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Differences in the Structure of Genetic and Environmental Contributions to Types of Peer Victimization

Abstract: Background: The goal of the present investigation was to clarify and compare the structure of genetic and environmental influences on different types (e.g., physical, verbal) of peer victimization experienced by youth in pre-/early adolescence and mid-/late adolescence. Method: Physical, verbal, social, and property-related peer victimization experiences were assessed in two twin samples (306 pairs, ages 9–14 and 294 pairs, ages 15–20). Cholesky decompositions of individual differences in victimization were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…(42% and 70%, respectively) versus social/relational (0% and 55%) and property-related victimization (0%, only in Eastman et al, 2018). In addition, the twin studies also seem to differ, for example, with regards to informants used and age of participants.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…(42% and 70%, respectively) versus social/relational (0% and 55%) and property-related victimization (0%, only in Eastman et al, 2018). In addition, the twin studies also seem to differ, for example, with regards to informants used and age of participants.…”
Section: Discussionmentioning
confidence: 99%
“…However, these variations could be accounted for by a variety of reasons. For instance, both Eastman et al (2018) and Veldkamp et al (2019) found that heritability estimates vary depending on the type of victimization; they found higher heritabilities for physical Residual scores from which the effects of grade, gender, group status and pre-intervention level of bullying or victimization were removed. A = additive genetic effects, D = dominant genetic effects, E = non-shared environmental effects including error.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations